Dynamics analysis of a cam with flat-bottomed follower system - Xiaorong Zhang; Guanwei Luo; Zheng Wang; Xinlei An; Fengwei Yin (Scientific Reports)
Abstract In response to the problem that the dynamic error caused by the elasticity of the follower rod should be taken into account when designing the cam profile, the form of contact between the cam and the follower rod is chosen in the paper as nonlinear Hertzian elastic contact. In order to obtain the expected movement of the follower rod, the dynamics of the system in the two-parameter planes of $$(ω ,{f_0})$$ , $$(ω ,{μ _{{\text{kn}}}})$$ and $$(ω ,{μ _{{\text{cn}}}})$$ are calculated to reveal the stable operation interval, the range of failure, and the reasonable parameter combinations. The transmigration processes between the movements n-p and n-(p + 1), n-p and (n + 1)-p as well as n-p and (n + 1)-(p + 1) and some special districts induced by them are discussed. Bifurcation diagrams, phase diagrams, and mapping diagrams are used to fully reveal the correlation between cam rotational speed, pressure, nonlinear contact stiffness, and contact damping and the dynamic performance of the system, while comparing the contact force as well as the depth of intrusion at various stages of the cam input curve. It is shown that the detachment of the cam and the follower rod mainly occurs at the beginning of far dwell phase and when the descent travel turns to the near dwell phase.